Upaya Memulihkan Kewibawaan Mahkamah Konstitusi Pasca Tertangkapnya Akil Mochtar - Sitabuana, Tundjung Herning (Jurnal Hukum IUS QUIA IUSTUM, 2016)
This research was to study and find an attempt to recover the authority of Constitutional Court after the apprehension of Akil Mochtar. The method used in this research was normatif legal research which was descriptive qualitative with statute approach. The secondary data were primary and secondary legal materials which were collected by literature study and analyzed normatively and qualitatively. The research result showed that the recovery of the authority of Constitutional Court must be conducted in a correct way, namely by using 1945 Constitution of Republic Indonesia as the guideline in order to ensure the implementation of the norms contained in 1945 Constitution as the standard. This was in accordance with the principle of constitution supremacy applied in Indonesia.